Learning microsoft cognitive services : use cognitive services APIs to add AI capabilities to your applications - Larsen, Leif (Packt Publishing Ltd, 2018)
This book will introduce you to the APIs released as part of Cognitive Services platform and show you how to leverage their capabilities. More importantly, you'll see how the power of these APIs can be combined to build real-world apps that have cognitive capabilities.